ANALYSIS OF STUDENT LEARNING MOTIVATION IN HISTORY SUBJECTS IN THE INDEPENDENT CURRICULUM AT SMKN 1 BANYUWANGI: ANALISIS MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DALAM KURIKULUM MERDEKA DI SMKN 1 BANYUWANGI - Anisatur Rosida; Riztika Widyasari; Totok Hari Prasetiyo; I Kadek Yudiana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Learning motivation is a driving factor that comes from within and outside of a person. With learning motivation, it is expected to improve students` achievement and learning outcomes. This research aims to describe student learning motivation in history subjects in the independent curriculum, as well as how the teacher`s role in increasing student learning motivation in history subjects at SMKN 1 Banyuwangi. The method used in this research is descriptive method with qualitative approach. The research subjects are the head of the curriculum, history teachers, and students. The data collection techniques that will be carried out are through observation, interviews, and documentations studies. Then the data is analyzed through 3 stages, namely data reduction, data presentation, and conclusion drawing. In the independent curriculum, educators are given flexibility in managing learning to adjust teaching according to the needs and conditions of students. Therefore, the role of educators is needed to increase student learning motivation so that they are interested in learning history. Based on the results of the analysis of student learning motivation in history subjects in the independent curriculum, it can be concluded that student learning motivation is good. This can be seen from the results of the acquisition of the percentage of students` intrinsic learning motivation of 41% in the good category, 34% in the excellent category, and 25% in the moderate category. Meanwhile, the results of the percentage of students` extrinsic learning motivation were 41% in the moderate category, 28% in the good category, 12,5% in the very good category, 12,5% in the poor category, and 6% in the very poor category. After the calculation, the overall average between intrinsic and extrinsic motivation is 64,23% with a good category